2017
DOI: 10.1002/pip.2900
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sb2Se3solar cell performance through theory-guided defect control

Abstract: Defects present in the absorber layer largely dictate photovoltaic device performance. Recently, a binary photovoltaic material, Sb2Se3, has drawn much attention due to its low‐cost and nontoxic constituents and rapid performance promotion. So far, however, the intrinsic defects of Sb2Se3 remain elusive. Here, through a combined theoretical and experimental investigation, we revealed that shallow acceptors, SeSb antisites, are the dominant defects in Sb2Se3 produced in an Se‐rich environment, where deep donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
148
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 32 publications
15
148
0
1
Order By: Relevance
“…Material and device characterization are similar to previous report 1, 2, 11 . XRD of Sb 2 Se 3 films was performed using a Philips X’Pert Pro diffractometer with Cu Kα radiation ( λ  = 1.54 Å).…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…Material and device characterization are similar to previous report 1, 2, 11 . XRD of Sb 2 Se 3 films was performed using a Philips X’Pert Pro diffractometer with Cu Kα radiation ( λ  = 1.54 Å).…”
Section: Methodssupporting
confidence: 74%
“…As reported by Tumelero et al 44 , the antisite defects dominated the distribution of defects in trichalcogenides due to the similar sizes of the constituent atoms. Our previous simulation also showed that Se Sb and antimony antisite (Sb Se ) are acceptor and donor defects, respectively 11 . Consequently, the E1 defect is most likely associated with the formation of Sb Se antisite defects.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Hall measurements prove that Sb 2 Se 3 films prepared by a fast thermal evaporation method present low conductivities of 10 −7 –10 −6 S cm −1 and a maximum hole concentration of 10 15 cm −3 if deposited in Se‐rich conditions. Transient absorption decay spectroscopy measurements demonstrate that the photocarrier lifetimes of Sb 2 Se 3 films are ≈102 ns . The mobility of Sb 2 Se 3 along the [0 0 1] direction can be as high as 20 cm 2 V −1 s −1 , and the electron diffusion length along the [0 0 1] direction under high illumination is 1.7 µm .…”
Section: Basic Properties Of Antimony Chalcogenide Materialsmentioning
confidence: 97%